THE EMERGENCE OF MULTIPLE ENGLISHES TREND, DO WE NEED A STANDARD ENGLISH? - Alfan Hariri (STKIP AL HIKMAH SURABAYA, 2024)
English has inevitably the global language that been used around the globe. According to Cristal there are approximately 1500 million people who use English from all sources; 750 million is first and second language speaker and the rest as foreign speaker. In the other word, there are one of the world population who are capable to use English. Interestingly, users of English as second and foreign language outnumbered the users of English as first language, which the ratio is 1:3 for native and non-native. Moreover, McArthur assumes that with the wide spread of new English trend, when they communicate together with their own New English, it will produce confusions and nonsenses among the speaker since they use unfamiliar English word in term of dialect and accents. To this purpose ministry of Singapore emphasizes the important of fostering standard English, not Singaporean English, especially in school to enable Singaporean communicate with people around the world. To sum up, standard English is now still urgent to be mastered since it is universally accepted for the world global communication.